2017
DOI: 10.1039/c6nr09005b
|View full text |Cite
|
Sign up to set email alerts
|

SERS-enhanced piezoplasmonic graphene composite for biological and structural strain mapping

Abstract: Thin-film optical strain sensors have the ability to map small deformations with spatial and temporal resolution and do not require electrical interrogation. This paper describes the use of graphene decorated with metallic nanoislands for sensing of tensile deformations of less than 0.04% with a resolution of less than 0.002%. The nanoisland-graphene composite films contain gaps between the nanoislands, which when functionalized with benzenethiolate behave as hot spots for surface-enhanced Raman scattering (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The surface energy of the substrate supports that graphene influenced the morphology of the nano-island films, and thus, a wide range of morphologies could be produced, from isolated islands to percolated networks. These graphene nano-island composite films exhibit tunable morphologies and small gaps between adjacent nano-islands, and could be transferred to flexible substrates [ 18 ].…”
Section: Solid-state Dewetting Of Thin Metal Films: Principle and mentioning
confidence: 99%
“…The surface energy of the substrate supports that graphene influenced the morphology of the nano-island films, and thus, a wide range of morphologies could be produced, from isolated islands to percolated networks. These graphene nano-island composite films exhibit tunable morphologies and small gaps between adjacent nano-islands, and could be transferred to flexible substrates [ 18 ].…”
Section: Solid-state Dewetting Of Thin Metal Films: Principle and mentioning
confidence: 99%
“… 17 This phenomenon is in contrast to metals, which typically have a positive TCR owing to an increase in both inelastic electron scattering and lattice spacing with temperature. 18 Given our previous experience with metal nanoislands on graphene as a platform for multimodal sensing, 2 , 19 we hypothesized that a zero-TCR sensor could be fabricated if the right amount of metal was deposited onto the graphene such that the effects of each material cancel each other out. To design this material, we characterized the effect of deposition thickness and island morphology on the TCR of the graphene–metal composites.…”
Section: Introductionmentioning
confidence: 99%
“…6,74,75,25,76,77,78 The role of graphene in the majority of these applications is as a substrate, allowing easy transfer onto arbitrary substrates for specific applications such as optical strain sensing using SERS (Figure 6c, d). 7 Additionally, it has been shown that graphene can also mitigate the effects of fluorescence in SERS signal-to-noise ratios. In recent work, the role of graphene has been expanded by exploiting its electrical conductivity to actuate musculoskeletal cells (Figure 6e, f).…”
Section: Optical Applicationsmentioning
confidence: 99%
“…Metal nanoislands on graphene have been used extensively as surface-enhanced Raman scattering (SERS) substrates with numerous applications such as structural strain mapping and time-dependent biological strain detection (c–g). (c–g) Reprinted and adapted with permission from reference 7 and the Royal Society of Chemistry. A silver nanoisland on graphene substrate on bent glass is depicted (c) with the SERS mapped area marked by the narrow yellow box and the apex of the bent glass marked by the white dashed line.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation